Forward and futures prices in a general equilibrium monetary model - Young, Leslie; Boyle, Glenn W. (Journal of Financial Economics, 1989)
Risk premiums on dollar-denominated forward and futures contracts depend on risk attitudes, consumption parameters, and the stochastic structure of money and outputs. Pure monetary uncertainty leads to forward market backwardation; pure output uncertainty leads to contango under high risk aversion. Similar conclusions hold for futures contracts if neither money nor output show negative serial correlation. The conflicting effects of money and output shocks can imply that each contract switches between contango and backwardation, that one contract shows contango when the other shows backwardation, and that capital losses are expected on one contract when capital gains are expected on the other.